Static planning models synthesis of quality improvement of software development process - Годлевский, Михаил Дмитриевич; Голоскокова, Анна Александровна (Eastern-European Journal of Enterprise Technologies, 2015)
The task of quality improvement planning of the software development process is presented in the form of the problem of rolling scheduling, which involves the formation of static and dynamic models. The synthesis of the static problem, which is multicriteria and based on the formalization of maturity model was considered in the paper. The utility functions of the extent of achieving the target profile and resource provision, necessary to accomplish the goal were used as criteria. Resource provision is determined by two generalized indicators. The first is finance, which are distributed among the individual structural components (practice and focus areas) of the software development process. The second - a resource indicator, is associated with the time the company employees must spend on advancing the software development process to a higher maturity level, that is, the time the employees are distracted from the company’s core activities. Three models that are focused on the following tasks: searching for a compromise with respect to various categories of the CMMI (Capability Maturity Model - Integrated) model and two sets of utility functions; defining a compromise with respect to the target integrated utility functions of two groups of criteria; searching for the optimal value of the generalized objective utility function were formed. The models are mathematical programming tasks with integer and Boolean variables.